Dynamic pathways between rejection and antisocial behavior in peer networks: Update and test of confluence model. (February 2020) - Kornienko, Olga; Ha, Thao; Dishion, Thomas J.
Abstract: The confluence model theorizes that dynamic transactions between peer rejection and deviant peer clustering amplify antisocial behavior (AB) within the school context during adolescence. Little is known about the links between peer rejection and AB as embedded in changing networks. Using longitudinal social network analysis, we investigated the interplay between rejection, deviant peer clustering, and AB in an ethnically diverse sample of students attending public middle schools (N = 997; 52.7% boys). Adolescents completed peer nomination reports of rejection and antisocial behavior in Grades 6–8. Results revealed that rejection status was associated with friendship selection, and adolescents became rejected if they were friends with others who were rejected. Youth befriended others with similar levels of AB. Significant patterns of peer influence were documented for AB and rejection. As hypothesized, rejected youth with low AB were more likely to affiliate with others with high AB instead of similarly low AB. In contrast, nonrejected youth preferred to befriend others with similarly high or low AB. Results support an updated confluence model of a joint interplay between rejection and AB as ecological conditions that lead to self-organization into deviant clusters in which peer contagion on problem behaviors operates.